David Draper: The making of a South African geologist (Historia, 2021)
David Draper was a South African geologist and key figure in the professionalisation of geology in the late nineteenth and early twentieth centuries. His biography demonstrates the importance of geology in South African political, economic and social history. This article traces Draper’s life from the mid-nineteenth century to the mineral discoveries and the South African War in the early twentieth century. It uses the figure of Draper to show the complexities and tensions in the creation of a South African identity that were themselves reflective of the political and ideological struggles of a nascent nation. It further argues that the history of geology cannot be divorced from the history of the country, mirroring the processes of colonial domination, conflict and ultimately, the creation of an independent state.
Keywords: David Draper; geology; science; 1820 settlers; South African War; Geological Society of Southern Africa; imperial history; Molengraaff